Design and Construction of Chassis Dynamometer for On-Site Testing of Tractors - Hasan Shahbazi; Aref Mardani; Arash Mohebbi; Sajjad Derafshpour (Biomechanism and Bioenergy Research)
Measuring tractor performance parameters is crucial for validating manufacturer claims and selecting a suitable tractor. Field studies often face high costs and inaccuracies due to external factors and limited parameter measurement. A chassis dynamometer serves as an effective simulator for tractor movement on the ground. This research focused on designing and constructing an in-situ test system (chassis dynamometer) with practical features for measuring parameters at various speeds, loads, and conditions. An accurate data acquisition system records unlimited data based on relations between drawbar traction, speed, vertical load on driving wheels, and the distance to the center of gravity. To evaluate the system, the traction performance of an MF285 tractor was tested at different load and speed levels. The drawbar pull and dynamic axle load of the 2WD tractor were measured, with a maximum traction of about 11 kN. This study successfully designed and implemented an in-situ test system to assess the traction and balance capacities of conventional tractors by applying maximum load on the driving wheels.